If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6s + -11 = -23 + 9s Reorder the terms: -11 + 6s = -23 + 9s Solving -11 + 6s = -23 + 9s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-9s' to each side of the equation. -11 + 6s + -9s = -23 + 9s + -9s Combine like terms: 6s + -9s = -3s -11 + -3s = -23 + 9s + -9s Combine like terms: 9s + -9s = 0 -11 + -3s = -23 + 0 -11 + -3s = -23 Add '11' to each side of the equation. -11 + 11 + -3s = -23 + 11 Combine like terms: -11 + 11 = 0 0 + -3s = -23 + 11 -3s = -23 + 11 Combine like terms: -23 + 11 = -12 -3s = -12 Divide each side by '-3'. s = 4 Simplifying s = 4
| 2x+13=10x+5 | | -17-3x=-50 | | -2v+10=2(5-v) | | x+3/2=9 | | (1-2q)-3=15 | | 435=32x+40 | | 6(3+2x)-3=63 | | -5x-16=-7+26 | | x+1/2=9 | | 2(3+6x)-1=41 | | 9+15z-7=9z+34-2z | | 9p+2.6=7.8+8p | | 7/1000= | | -42-4c=2c | | 9(4x-1)=3(12x+3) | | 56(7x-3)+78=6(7-3x)-78 | | 9/50= | | 9+4r-7=6r+14-4r | | 17w-2=15w | | 16(x^2+11x+36)=0 | | 1.2=0.4y | | 5t-11=2t-5 | | -5y+5=-9y | | -17w-2=15w | | 0.7*2.4+16+4*2.4=27.28 | | x+3=2/9 | | 11/20= | | 2m+9m=33 | | 3.33=-3(9+n) | | 8x+1=7x-20 | | 50/100= | | 5x+3(10)=3.5(x+10) |